Effect of radial impeller size in the presence and absence of baffles on the copper exchange on zeolite NaX - Svilović, Sandra, kemičarka (Array, 2021)
Effect of hydrodynamics on ion exchange in a batch reactor is still not appropriately studied even though proper mixing parameters may considerably affect the process of solid suspension and its costs. In this work, hydrodynamic conditions generated by straight blade turbine (SBT) impellers on suspension in the batch reactor with and without baffles were investigated. The aim of this work was to analyze influence of impeller diameter and zeolite mass on just suspended impeller speed, (NJS) power consumption, maximum amount of copper exchanged onto zeolite NaX and copper exchange kinetics as well. All experiments were conducted at the same temperature, initial concentration of the copper solution and zeolite particle size. The obtained results showed that just suspended impeller speed decreases as impeller diameter increases in the reactor with and without baffles but this trend is considerably more pronounced in the reactor with baffles. The increase in zeolite mass causes a slight increase of NJS in the both reactor. In the reactor with the baffles this increment became noticeably higher as impeller diameter decrease. Power consumption, at the state of complete zeolite suspension, decreases as impeller diameter increases and its values in the reactor without baffles are considerably lower as well. Kinetics results indicated that the amount of copper ion increases significantly in the initial stage and then gradually until the equilibrium is reached for all hydrodynamics conditions and mass of zeolite examined.